A determination methodology for the spatial profile of the convective heat transfer coefficient on building components. Issue 4 (April 2018) - Vereecken, Evy; Janssen, Hans; Roels, Staf
Several experimental procedures have been established to determine the convective heat transfer coefficient, a frequently used parameter in many engineering disciplines. Almost all of these methodologies focus on point or spatially averaged values. Yet, in many studies the spatial profile of the local convective heat transfer is of importance. In this paper, a methodology to determine such spatial profile is proposed. In this method, experiments are combined with Monte Carlo simulations. Such an approach makes it possible to account for inaccuracies in the input data. As an example, the methodology is applied to determine the spatial profile of the local convective heat transfer coefficient near a corner for two thermal bridge configurations. The temperature difference between interior surface and indoor air is found to restrict the applicability of the method. Nonetheless, for the case with a sufficient temperature difference, the order of magnitude of the convective heat transfer coefficients further away from the corner is in line with literature data. An important limitation of the technique at this stage of its development is, however, its requirement for prior knowledge of the equation that describes the spatial profile of the convective heat transfer coefficient. Despite these drawbacks, the methodology shows much potential and can be valuable for other applications as well.